Rhodium as the promising material for the first mirrors of laser and spectroscopy methods of plasma diagnostics in a fusion reactor - Orlinski, D.; Bardamid, A.F.; Konovalov, V.; Kedrov, V.; Klassen, N.; Shtan, A.; Shapoval, A.; Solodovchenko, S.; Strukov, G.; Voitsenya, V.; Vukolov, K.; Yakimov, K. (Вопросы атомной науки и техники, 2000)
To introduce a visible radiation into plasma or to extract radiation from the vessel of a fusion device it is necessary to use the set of mirrors the first of which does directly see the hot plasma. It will undergo all types of plasma radiation– electromagnetic, nuclear and particle fluxes. The most dangerous for mirror surface will be the bombardment by particles. To have an optical system in a working state it is necessary to choose the first mirror (FM) material, which will assure to maintain the mirror optical properties for as long time as required. The aim of this work is testing rhodium as the FM material which, as known beforehand, is one of the stable materials under particle impact and has a quite high reflectance. Because of high cost, Rh cannot be used as a solid piece for FM fabrication, and it is necessary to deposit Rh layers (<10 mm) on substrates of appropriate metals. In the presented report the results of experiments on fabricating Rh mirrors and testing their properties are discussed.